A Comprehensive Research Review Regarding the Material Behavior of Concrete Filled Double Skin Tubes - Cintantya Budi Casita; Data Iranata; Budi Suswanto; Masahide Matsumura (Jurnal Teknologi dan Manajemen, 2024)
This study provides a detailed investigation of the material behavior of concrete-filled double-skin tubes (CFDST). The research primarily focuses on the development and examination of cross-sectional variations, stress-strain relationships in the materials, and their corresponding characteristics. By conducting a comprehensive study and evaluation, this research endeavors to provide a more profound comprehension of the impact of this particular behavior on the overall responsiveness and capacity of materials. The influence of various parameters on a variety of cross-sectional configurations, comprising circular outer and circular inner tubes (C-C), circular outer – square inner tubes (C-S), square outer – circular inner tubes (S-C), square outer – square inner tubes (S-S) have been recently examined in earlier research. Furthermore, this study discusses additional evaluations consisting of sandwiched concrete and the inner and outer steel components. Despite the substantial study conducted by CFDST, there is presently a lack of established guidelines or regulations pertaining to the design of composite structures. Consequently, it is imperative to acquire a comprehensive comprehension of the behavior exhibited by these materials. This understanding serves as essential for the development of design rules specific to CFDST composite structures. By performing consequently, the outcomes of this study can be effectively employed in the design, analysis, and optimization of the distinctive attributes associated with composite materials.